Effects of 6-mercaptopurine and its derivatives on human hepatocellular carcinoma and mammary adenocarcinoma cell lines - Hakim, Muhammad Nazrul; Hong, Mak Jun; Keong, Yong Yoke; Ahmad, Zuraini (Science Alert, 2024)
Background and Objective: The 6-Mercaptopurine (6-MP) is used to treat autoimmune diseases and inflammation such as rheumatoid arthritis, Crohnʼs disease and ulcerative colitis. It is also very useful for acute leukemia in children. Therefore, the objective of this present study was to evaluate the cytotoxicity potential of 6-MP and its derivatives 6-Hydroxy-2-Mercaptopurine (6H2MP) and 2-amino-9-butyl-6- mercaptopurine (2A9B6-MP) on other cancer cells. Materials and Methods: The HepG2 cells, a cell line derived from human hepatocellular carcinoma and MCF-7 cells, a cell line derived from adenocarcinoma of mammary gland epithelial cells, were incubated in vitro with these three 6-MP derivatives and the cytotoxic potential was measured using 3-(4,5-Dimethylthiazole-2-yl)-2, 5-Diphenyltetrazolium Bromide (MTT) assay. Results: The incubations revealed HepG2 cells were more susceptible to all derivatives when compared to MCF-7 cells. THe 6-MP was cytotoxic when compared to the other 2 related compounds. The HepG2 cells were only at 37.20 and 19.50% viable at 50 and 100 M concentration of 6-MP, respectively. Whereas, MCF-7 cells were at 60.31 and 55.41% viability at the same 6-MP concentration respectively. Viability of HepG2 cells were at 67.51 and 53.20% at the 2 highest concentration of 6H2-MP and MCF-7 showed better viability at 82.71 and 79.95% at 50 and 100 M concentration of 6H2-MP, respectively. The MCF-7 was also more resistant to 2A9B6MP where the viability of MCF-7 cells was approximately double to the viability of HepG2 at 100 M 2A9B6-MP. Conclusion: Analogues of 6-MP appeared to be less toxic to cancer cells when compared to 6-MP. The 6-MP is useful in the treatment of leukemia clinically and from this current study, the usefulness may extend to liver cancers. However, further investigations are needed to exactly evaluate the effectiveness of 6-MP in liver cancers.